Severity and duration of immune response in people of different age categories after SARS-CoV-2 revaccination - O. M. Drapkina; S. A. Berns; M. G. Chashchin; A. Yu. Gorshkov; O. V. Zhdanova; L. N. Ryzhakova (Кардиоваскулярная терапия и профилактика)
The article discusses the effectiveness and safety of homologous and heterologous revaccination for Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in people of different age groups.Aim. The study the severity and duration of immune response in people of different age groups after SARS-CoV-2 revaccination.Material and methods. The study was carried out as part of the prospective registry Saturn, which included persons who received various SARS-CoV-2 revaccination regimens (homoand heterologous) based on the combination of two vaccines: Gam-COVID-Vac and Covivac. Group I (n=106) included persons who received a homologous revaccination with Gam-COVID-Vac, while group II (n=54) — heterologous revaccination with Gam-COVID-Vac and Covivac, group III (n=40) — homologous Covivac revaccination. In addition, all participants in the study were divided into two age categories: ≥60 years (n=33) and <60 years, (n=167). In all participants, the medical history was collected. At each visit, we assessed the quantitative level of specific IgG SARS-CoV-2 S-protein antibodies and plasma coagulation using the thrombodynamics method. At visits 1, 3 and 5, blood was collected to assess T-cell immunity activity (T-Spot.COVID test, Oxford Immunotec) to the SARS-CoV-2 virus.Results. Revaccination in persons ≥60 years of age ensures the intensity of humoral (quantitative level of specific IgG SARS-CoV-2 S-protein antibodies) and cellular immunity (quantitative assessment of SARS-CoV-2 spike protein-specific (panel A) and nucleocapsid-specific T-lymphocytes) comparable to that in younger individuals (<60 years). Revaccination did not increase the plasma thrombogenic potential in vaccinated people, regardless of age.Conclusion. In the group of vaccinated people ≥60 years old, an adequate humoral and cellular immune response was developed, which persisted for a year after revaccination, and even more intense cellular immunity was demonstrated compared to vaccinated people <60 years old. The plasma thrombogenic potential did not increase during vaccination and revaccination, regardless of age.